1978
DOI: 10.1136/bjo.62.6.373
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic keratitis: a clinicopathological case report.

Abstract: SUMMARY A 22-year-old farmer with recurrent corneal erosions and keratoiritis underwent a penetrating keratoplasty. Investigations carried out on the corneal disc revealed an amoebic keratitis, which is considered to be a very rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
6

Year Published

1980
1980
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 0 publications
0
12
0
6
Order By: Relevance
“…It is tempting to assume, that all previous cases have been misdiagnosed, but a retrospective study carried out in the Lon don Institute of Ophthalmology revealed no new cases of amoebic infections among the 756 cases of keratitis or corneal ulcerations reported over a period of 15 years [4], Like wise, in the 172 cases registered in the Uni versity Eye Clinic of Munich, no other cases with amoebic cysts were found [6], Griffin [12], however, reported that samples sub mitted to the American Forces Institute of Pathology contain material similar to the re ported Acanthamoeba eye infections, thus suggesting that these infections are not so rare. As mentioned before, a new case of Acanthamoeba eye infection has recently been recognised in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is tempting to assume, that all previous cases have been misdiagnosed, but a retrospective study carried out in the Lon don Institute of Ophthalmology revealed no new cases of amoebic infections among the 756 cases of keratitis or corneal ulcerations reported over a period of 15 years [4], Like wise, in the 172 cases registered in the Uni versity Eye Clinic of Munich, no other cases with amoebic cysts were found [6], Griffin [12], however, reported that samples sub mitted to the American Forces Institute of Pathology contain material similar to the re ported Acanthamoeba eye infections, thus suggesting that these infections are not so rare. As mentioned before, a new case of Acanthamoeba eye infection has recently been recognised in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Some time later, we had the opportunity to study the case of Lund et al [6], in whom Acanthamoeba castellanii had been identified. The authors of that report were familiar with our case, and we were able to observe that the organisms in their slides were, at least light microscopically, identical with those of our case.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypopyon, hyphema, and uveitis may be present as well (119). Histologic examination demonstrates the presence of both trophozoites and cysts in the cornea (113,119,131,162,295). It has been postulated that the intense inflammation associated with Acanthamoeba keratitis occurs only after the death of the parasite (138).…”
Section: Ocular Disease Caused By Protozoansmentioning
confidence: 99%
“…In the Federal Republic of Germany, so far two cases of amoebic keratitis due to acanthamoebae have been noted (LUND et al, 1978;WITSCHEL et al, 1984). The best known species belong to the genera Naegleria and Acanthamoeba.…”
Section: Primary Amoebic Meningo-encephalitis (Pame) and Granulomatoumentioning
confidence: 99%